Cover Feature: Thermally Induced trans‐to‐cis Isomerization and Its Photoinduced Reversal Monitored using Absorption and Luminescence: Cooperative Effect of Metal Coordination and Steric Substituent (Chem. Eur. J. 20/2019). Issue 20 (12th March 2019) - Zhang, Jun‐Quan; Zhang, De‐Shan; Chen, Qiu‐Jie; Xu, Hai‐Bing; Kurmoo, Mohamedally; Zeng, Ming‐Hua
Abstract : Cooperative effect : This cover artwork is inspired by the ancient Chinese myth of "King Yi Shooting Down Nine Suns". In the picture, bamboo represents the trans ‐isomer of the ligand. After chelation of metallic ions with trans ‐ligands under solvothermal condition, a cis ‐LM II Cl2 could be formed. Similarly, a bow, which stands for the cis ‐LM II Cl2, is made from pieces of bamboo and rope under hot temperatures. Just as the spectra discrepancy between cis ‐LM II Cl2 and trans ‐isomer is sharply magnified, the bow can send arrows far away, as the legend goes, even to shoot the other nine suns down. More information can be found in the Full Paper by H.‐B. Xu, M.‐H. Zeng, et al. onpage 5177 .